Food marketing with movie character toys: Effects on young children's preferences for unhealthy and healthier fast food meals. (1st October 2017) - Dixon, Helen; Niven, Philippa; Scully, Maree; Wakefield, Melanie
Abstract: This study aimed to test whether movie tie-in premiums (MTIPs) accompanying unhealthy and healthier fast food meals influenced children's meal preferences and their perceptions of these meals. Nine hundred and four Grade 1 and 2 students (aged 5–9 years) from Melbourne, Australia participated in a between-subjects online experiment comprising the following conditions: (A) unhealthy and healthier meals with no MTIP (control); (B) unhealthy and healthier meals with MTIP (current situation in Australia); (C) unhealthy meals with MTIP and healthier meals without MTIP; (D) unhealthy meals without MTIP and healthier meals with MTIP. The latter condition tested a potential regulatory model restricting premiums to healthier meals. Participants were shown a trailer for a current children's movie followed by an advertisement for an associated McDonald's Happy Meal ® (conditions B-D) or an advertisement for a children's leisure activity (condition A). They were then shown four McDonald's Happy Meal ® options on screen and asked to select their preferred meal before completing detailed meal ratings. Overall, children showed a preference for unhealthy meals over healthier ones. Children were significantly more likely to select a healthier meal over an unhealthy meal when only the healthier meals were accompanied by a MTIP (condition D) compared to the other three conditions. When healthier meals were accompanied by a MTIP, children reported the meal looked better, would taste better, they would be more likely to ask their parents for this meal, and they would feel happier if their parents bought them this meal, compared to when the healthier meal was not accompanied by a MTIP. Results suggest that modifying the food marketing environment to restrict MTIPs to healthier meals should encourage healthier fast food meal choices by children.